Social work students’ perceptions of volunteering It is a field research within Sulaimani University - Karim, Asst.L. Sazan Hama Saeed (Sulaimani Journal for Humanities, 2026)
Volunteering is now seen as a necessity for human coexistence. Volunteering is not only providing material assistance to the poor, it has expanded to other social and psychological aspects The main objective of this research is to involve young people in general and university youth in particular, by obtaining their opinions on the issue and the most important areas of volunteer work and what obstacles to youth participation, this research consists of three main parts: Part 1 / General Research Framework (Problems, Importance and Objectives) Part 2 / Theoretical Framework of the Research (Description of Scientific Theory in Volunteering) Part 3 / Research Methodology (The type of this research is descriptive analysis, the research community are students of the Department of Social Work in Sulaimani University who were randomly recruited from the main community, using information forms and measuring through statistical criteria known as (measurement). The most important results of this study are that there is a great desire among university youth to participate in volunteer work and currently the opportunity to participate is not available.